Mengasah Jiwa Wirausaha Anak Panti melalui Kreasi Clay dan Digital Marketing Sederhana - Julianto, Alven; Juniwati, Juniwati; Apriyadi, Ridho Nur; Saputra, Wira; Rahayu, Nika Gita; Ramadani, Lusi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The program “Sharpening the Entrepreneurial Spirit of Orphanage Children through Clay Creation and Simple Digital Marketing” is a form of empowerment for children at the Muhammadiyah Tunas Melati Orphanage in Pontianak City in facing social and economic challenges in the digital era. The program aims to instill an entrepreneurial spirit from an early age through a combination of creative skills and the use of digital technology. Using a participatory and hands-on approach (Participatory Learning and Action), 23 orphanage children aged from elementary school to high school were equipped with an understanding of their potential, clay craft-making skills, and digital promotion training using Canva. The activities consist of three main stages: mapping dreams and strengthening self-management, digital literacy education and social media ethics, as well as an introduction to AI, and entrepreneurship training through product creation and promotional design. The results of the activities show a significant increase in self-confidence, creativity, cooperation, and awareness of technology-based business opportunities. The children were able to produce marketable works and understand moral values such as courage, perseverance, and independence. The program was deemed effective in fostering an adaptive and competitive entrepreneurial mindset. It is hoped that this program can be replicated in other social institutions as a model for sustainable community empowerment based on local potential and digital technology.